Cairo Now: City Incomplete, Curator & Editor: Mohamed ElShahed/ (3bGgQI(B! (3eOjfI ZjQ ecJedI s (Dubai Design Week, 2016)
Exhibition catalog. Design in and around the city of Cairo. Includes calligraphy, architecture, graphic design, etc. Translators: Amira ElMasry, Peter Halim, Ebtihal Makhlouf.
English; Arabic
Keywords: N7560-8266 Visual Arts. Special subjects of art; Egypt -- Cairo